Hot corrosion behavior in thermal barrier coatings with heterogeneous splat boundary. (February 2020) - Song, Dowon; Song, Taeseup; Paik, Ungyu; Lyu, Guanlin; Jung, Yeon-Gil
Highlights: Hot corrosion behavior of YSZ/LZO blended TBC was investigated. YSZ/LZO blended layer produced LaVO4, m -ZrO2, and t -ZrO2 in a hot corrosive environment. The blended layer showed a shallow infiltration depth and a severely degraded microstructure. The corrosion mechanism has been suggested in the blended TBC with a heterogeneous interface. Abstract: In the present study, layered thermal barrier coatings (TBC) were fabricated with different surface layers with lanthanum zirconate (LZO), yttria-stabilized zirconia (YSZ), and YSZ/LZO blended layer. Their hot corrosion behaviors were investigated in the molten salt of Na2 SO4 + V2 O5 at 1100 °C. TBC with the YSZ/LZO blended layer showed a different hot corrosion behavior with a relatively shallow depth and densified reaction layer compared with those with the LZO and YSZ layers. The blended layer showed the most severely degraded microstructure above the planar reacted area, which can be more appropriate for a sacrificial layer to protect the substrate.